(untitled) (Journal of Pathology of Nepal, 2019)
Background: Odontogenic cysts are defined as the epithelial cysts which arise from odontogenic epithelium and occur in tooth bearing regions of jaws. The objective of the present study was to analyze different histopathological types of cystic jaw lesions and to determine the distribution of their relative frequency according to site, sex, size and age group. Materials and methods: This study was a cross sectional hospital based observational study conducted in the Department of Pathology, Manipal Teaching Hospital. All cases with cystic jaw lesions on histopathology during the study period from January 2014 to December 2018 were included in the study. Results: Thirty-two cases of cystic jaw lesions were reported during the study period. Females were more commonly affected in our study with a male: female ratio of 1:1.9. The age range in the study was 9 to 71 years with a mean age of 33.3 years. The most frequent type was radicular cysts followed by dentigerous cysts, odontogenic keratocysts and cystic ameloblastoma. Radicular cysts showed the most female predilection with a ratio of 1:4.3. and a mean age of 35.6 years. Majority of dentigerous cysts were seen in patients below 30 years. Both radicular cysts and dentigerous cysts showed more involvement of maxilla but odontogenic keratocysts were more common in mandible Conclusions: The present study corroborate with other similar literature with respect to the frequency percentage of different types of jaw cysts.However, female predilection was seen in radicular and dentigerous cysts. Maxilla was the more common site except in odontogenic keratocysts.